2022
DOI: 10.1111/ijal.12439
|View full text |Cite
|
Sign up to set email alerts
|

Autonomous use of podcasts with metacognitive intervention: Foreign language listening development

Abstract: Podcasts have become a pervasive and easy-to-access input for language learning that may improve both form and meaning aspects of language. This study attempted to investigate some unknown impacts of the autonomous use of podcasts through a metacognitive intervention on 12 adult language learners' listening comprehension with an exploratory approach and using a questionnaire, learners' journals, and semi-structured interviews. The results suggest that autonomous language learners may benefit from multiple adva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
(57 reference statements)
0
5
0
1
Order By: Relevance
“…Podcasts can help language learners in a variety of ways, including by enhancing their vocabulary, grammar, pronunciation, and listening comprehension. Podcasts can help students learn a variety of language skills, including grammar, pronunciation, and vocabulary, in addition to speaking and listening (Bozorgian & Shamsi, 2022). For language learners, podcasts can offer authentic and interesting material as well as chances for independent, self-directed learning.…”
Section: Using Podcast Materials To Enhance Vocabulary Buildingmentioning
confidence: 99%
“…Podcasts can help language learners in a variety of ways, including by enhancing their vocabulary, grammar, pronunciation, and listening comprehension. Podcasts can help students learn a variety of language skills, including grammar, pronunciation, and vocabulary, in addition to speaking and listening (Bozorgian & Shamsi, 2022). For language learners, podcasts can offer authentic and interesting material as well as chances for independent, self-directed learning.…”
Section: Using Podcast Materials To Enhance Vocabulary Buildingmentioning
confidence: 99%
“…It is how they can expand their vocabulary. These skills will be used by the students to explain their intentions to others (Bozorgian & Shamsi, 2023). They learn how to give a clear description of something by studying monologue materials.…”
Section: Manipulating Monologue Podcast Contentmentioning
confidence: 99%
“…Podcasts provide a dynamic and immersive learning environment by exposing students to real-world language, giving interesting and contextualized learning opportunities, delivering a variety of content, promoting vocabulary growth, and improving listening skills. As technology develops, using podcasts as a tool for language learning can surely hasten the process of language acquisition and provide students with the abilities they need to speak effectively in the target language (Bozorgian & Shamsi, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…As regards self-access listening, prior studies attempted to increase students' listening exposure beyond the classrooms with the support of a wide array of technological tools from different perspectives. Specifically, Bozorgian and Shamsi (2022) investigated the impacts of the autonomous application of podcasts on 12 adult language learners' listening comprehension. The intervention focused on the use of metacognitive strategies by the students who listened extensively via the podcasts.…”
Section: Previous Related Studies In Autonomous Listeningmentioning
confidence: 99%
“…A review of the literature has shown that most studies about SALL focus on language learning in general (e.g., Chung, 2013;Diaz, 2016;Gardner & Miller, 2011;Gardner & Yung, 2017;Morrison, 2008). Regarding self-access listening, prior studies attempted to increase students' exposure to listening outside the classrooms with the aid of a technological tool, such as podcasts (Bozorgian & Shamsi, 2022), Google Classrooms (Melani, 2020), TED Talks (Yang, 2021), mobile devices (Fatimah et al, 2021), etc. Others underscore metacognitive awareness for fostering autonomous listening, including listening logs (Kemp, 2009), self-assessment, and reflection (Ngo, 2020).…”
mentioning
confidence: 99%